JNK2 mediates TNF-induced cell death in mouse embryonic fibroblasts via regulation of both caspase and cathepsin protease pathways. - Dietrich, N; Thastrup, J; Holmberg, C; Gyrd-Hansen, M; Fehrenbacher, N; Lademann, U; Lerdrup, M; Herdegen, T; Jäättelä, M; Kallunki, T (2004)
Recent studies strongly suggest an active involvement of the c-Jun N-terminal kinase (JNK) signaling pathway in tumor necrosis factor (TNF)-induced apoptosis. The direct evidence for the role of JNK and its isoforms has been missing and the mechanism of how JNK actually could facilitate this process has remained unclear. In this study, we show that Jnk2-/- primary mouse embryonic fibroblasts (pMEFs) exhibit resistance towards TNF-induced apoptosis as compared to corresponding wild-type and Jnk1-/- pMEFs. JNK2-deficient pMEFs could be resensitized to TNF via retroviral transduction of any of the four different JNK2 splicing variants. Jnk2-/- pMEFs displayed deficient and delayed effector caspase activation as well as impaired cytosolic cystein cathepsin activity: processes that both were needed for efficient TNF-induced apoptosis in pMEFs. Our work demonstrates that JNK has a central role in the promotion of TNF-induced apoptosis in pMEFs, and that the JNK2 isoform can regulate both mitochondrial and lysosomal death pathways in these cells.